Methods of drying beef and buffalo meat on meat quality (Bangladesh Veterinarian, 2010)
Effects of method of drying beef and buffalo meat and storage time on quality were investigated. Six treatments were applied: drying beef with salt (B1), drying beef without salt (B2), drying beef with salt and spices (B3), drying buffalo meat with salt (B4), without salt (B5) and with salt and spices (B6). Taste and smell of all samples were acceptable up to 120 days of storage. The dry matter (DM), protein, ether extract (EE) and ash content decreased with storage time. The initial DM, crude protein (CP), EE and ash content of the samples were 92.1-95.2%, 77.0-78.6%, 5.0-6.5%, 8.0-12.8%, respectively. After 120 days of storage DM, CP, EE and ash content of the samples ranged from 87.8-89.1%, 72.9-74.0%, 5.0-5.9%, 7.4-9.7%, respectively. CP and EE percentage in beef was higher than buffalo meat, but beef contained less DM and ash. At the end of storage beef dried with salt contained highest protein (74.0%) and buffalo meat dried without salt contained lowest protein (73.0%). There was a significant (p